2013
DOI: 10.11648/j.jfns.20130104.11
|View full text |Cite
|
Sign up to set email alerts
|

Taste Compounds from Crude Extract of Bekkai lan (Albertisia papuana Becc.)

Abstract: Bekkai lan leaves are commonly known as food flavoring in the culinary world of Dayak tribe, Borneo, Indonesia. No report has been made concerning the profile of the taste compounds in the extract of bekkai lan leaves. Thus, this study was aimed to investigate the profile of taste compounds in the leaves. The experiment was conducted on the crude extract of homemade leaves powder by using HPLC method. The results showed that the total content of taste compounds was 73.72 mg/g and there were 22 selected taste c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Monosodium glutamate (MSG), guanosine monophosphate (GMP), and inosine monophosphate (IMP) are instances of umami chemicals that can be encountered in their salt forms under conditions of neutral pH. The employment of glutamate as a flavor enhancer within a pH range of 5 to 8, encompassing slightly acidic to neutral circumstances, has been substantiated by the findings of [32]. Furthermore, it has been noted that the ionic milieu around the cells of taste buds influences the interplay between the chemicals responsible for producing flavors and the receptor cells.…”
Section: Nucleotidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Monosodium glutamate (MSG), guanosine monophosphate (GMP), and inosine monophosphate (IMP) are instances of umami chemicals that can be encountered in their salt forms under conditions of neutral pH. The employment of glutamate as a flavor enhancer within a pH range of 5 to 8, encompassing slightly acidic to neutral circumstances, has been substantiated by the findings of [32]. Furthermore, it has been noted that the ionic milieu around the cells of taste buds influences the interplay between the chemicals responsible for producing flavors and the receptor cells.…”
Section: Nucleotidesmentioning
confidence: 99%
“…One noteworthy category for examination is the Kalimantan endemic plants, which have played a significant role as a natural flavoring source [39]. The Menispermaceae family encompasses a variety of plant species, such as Pycnarrhena tumefacta Miers, Albertisia papuana Becc, and Pycnarrhena cauliflora (Miers) Diels [12,32,40]. The findings indicated that plants belonging to the Menispermaceae family possess secondary metabolites, specifically flavonoids, alkaloids, steroids, saponins, and phenolics [12,13,41].…”
Section: Umami Peptidesmentioning
confidence: 99%
See 1 more Smart Citation